2006
DOI: 10.1021/nl052396o
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Size and Shape Dependence of Gold Nanoparticle Uptake into Mammalian Cells

Abstract: We investigated the intracellular uptake of different sized and shaped colloidal gold nanoparticles. We showed that kinetics and saturation concentrations are highly dependent upon the physical dimensions of the nanoparticles (e.g., uptake half-life of 14, 50, and 74 nm nanoparticles is 2.10, 1.90, and 2.24 h, respectively). The findings from this study will have implications in the chemical design of nanostructures for biomedical applications (e.g., tuning intracellular delivery rates and amounts by nanoscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

235
3,748
21
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,359 publications
(4,095 citation statements)
references
References 36 publications
235
3,748
21
20
Order By: Relevance
“…36,37 Chan's group has shown that spheres, in particular 50 nm sized GNPs, are taken up to a significantly greater extent than rods, independently of their aspect ratio. 28,29 This observation has been confirmed by other studies. 38 So far, only two shapes (spheres vs rods) have been compared in terms of internalization.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…36,37 Chan's group has shown that spheres, in particular 50 nm sized GNPs, are taken up to a significantly greater extent than rods, independently of their aspect ratio. 28,29 This observation has been confirmed by other studies. 38 So far, only two shapes (spheres vs rods) have been compared in terms of internalization.…”
supporting
confidence: 84%
“…In our studies, CTAB-coated gold spheres (10 11 GNPs/mL) lead to marked neural cell loss 24 h after exposure, while CTAB-coated gold rods exhibited a more modest reduction in viability, likely due to the increased uptake of spheres supporting the findings by Chan's group. 29 Dark-Field Microscopy and Hyperspectral Analysis of Gold Nanoparticles in Microglial Cells. Next, we performed intracellular imaging of GNPs using high contrast dark-field imaging ( Figure 3 and Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Gold nanoparticles, including nanorods in this size range, have applications in industrial catalysis, chemical sensing and pharmaceutical technologies, and it is known they can be taken up by cells in culture [19][20][21][22][23] . This work reports the fate of gold nanoparticles in a complex ecosystem containing sediments, biofilms, primary producers, filter feeders, grazers and omnivores.…”
Section: Nmmentioning
confidence: 99%
“…Previous studies have reported the internalization of chemically derived gold nanoparticles into several cell lines within 48 h or less, presuming or proving an endosomatic localization for the incorporated particles (8)(9)(10)(11). The latter raises the problem of transporting the particles into the cytosol to gain access to the location of interest.…”
Section: Introductionmentioning
confidence: 99%